WorldSkills as means of improving quality of pedagogical staff training - Venediktovna Smirnova, Zhanna; N. Zanfir, Ludmila; Igorevna Vaganova, Olga; Vasilevna Bystrova, Natalia; Vladimirovna Frolova, Nina; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
Today the problem of identifying and developing talents in children and youth is extremely urgent. One of the priorities is the formation of a creative person who is able to freely and boldly meet any obstacles and difficulties in his path, the one who has deep, constantly updated and developing knowledge. This is especially important for graduates of educational institutions that are trained in working professions and must be competitive in the labor market. The article considers one of the most important tools in implementing a set of measures aimed at improving the vocational education system which is the participant in the WorldSkills movement. We conducted a formative experiment involving 20 students from Minin Nizhny Novgorod State Pedagogical University. The purpose of the experimental work was the system of formation and development of professional skills competitions in accordance with WorldSkills standards. Therefore, this article discusses the development of new educational programs that are effectively used in the methods and technologies of training students to enable them to participate in national and international competitions of professional skills WorldSkills, applying the technology of development of the system of teacher education with the use of the WorldSkills movement in vocational training pedagogically frames. Guided by the results of experimental work they came to the conclusion that the holding of the WorldSkills professional mastery competitions for the preparation of future technology teachers became a motivating factor in the learning process as a whole, while studying the discipline, interest in self-study, self-assessment and self-assessment of knowledge and skills are developed.